Characterisation of a mutant mouse model of spontaneous atopic dermatitis - Moran, Tara (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2017)
Atopy is Immunoglobulin-E sensitisation to “allergens” such as pollen and food. Atopic dermatitis is a pruritic eczematous dermatitis associated with an early onset in infants. Atopic dermatitis has a complex pathology and is influenced by factors such as skin barrier dysfunction, aberrant immune responses, genetics and environmental stimuli. The pathogenesis of atopic dermatitis remains to be fully elucidated with current research attempting to identify the primary driving factors in this disease. The skin itself has been implicated as the initiator of disease by triggering a cascade of immune responses that promote, or are the consequence, of skin barrier disruption. Genetic studies have identified null mutations in FLG, encoding the skin protein filaggrin, as a risk factor in the development of atopic dermatitis and further implicating a primary role of the skin barrier in this condition
Embargo End Date: 2023-02-01
Keywords: Medicine, Ph.D.; Ph.D. Trinity College Dublin, 2017